Penyuluhan Hukum pada Warga Muhammadiyah dalam Aspek Tanah Wakaf di Kabupaten Sorong Perspektif Kepastian Hukum - Moh Ery Kusmiadi; Munzir Munzir; Muhammad Rochib Mustaqim; Nadila Nadila (Universitas Muhammadiyah Semarang, 2024)
The Muhammadiyah organization, as one of the largest Islamic organizations in Indonesia, has many waqf land assets throughout the country, including in Sorong district, West Papua Province. Waqf land assets owned by Muhammadiyah in Sorong Regency have great potential to provide benefits to the local community, but despite the enormous potential value, the management of waqf land is often faced with a number of problems that can hinder the achievement of waqf goals. Problems with partners in service that occur in the field include a lack of understanding and awareness, many Muhammadiyah residents do not have adequate understanding and knowledge about the concept of waqf land. Complicated administration and access to legal aid, administrative processes related to waqf land, including licensing and monitoring are often complicated and time consuming. The method of implementing the service is in the form of counseling, workshops and training located at the Muhammadiyah Regional Leadership Office or Hall in Sorong Regency. The results of the service are (1) With the existence of special autonomy for Tanah Papua or Sorong so that the customary laws that apply in that area make it possible for several things to become challenges and obstacles for the service team, lecturers and students, (2) The members of the Muhammadiyah organization still lack human resources. who have an advocate background or work as a lawyer, (3) Incomplete data on waqf land means that the service process is not yet comprehensive in carrying out outreach aspects to Muhammadiyah members who have waqf land with problems or disputes in the customary legal process of the Papuan people.